One-way moisture-conducting biodegradable non-woven fabric and preparation method thereof
By preparing the nano -particles into a nucleus to prepare the wood -beanized nanoparticles on the lignin, and use the low -temperature plasma technology to modify it, it solves the heat resistance and crystallization performance of biodegradable plastics in the spinning process. The improvement of unidirectional wetness performance and the breathability of non -woven fabrics.
Patent Information
- Application Number
- CN202411705372.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
During the spinning process, biodegradable plastics have problems such as poor heat resistance and poor crystallization performance, which leads to the inability to draw and lay the net normally. The preparation method of one-way guide wet non-woven fabrics is complicated, affecting breathability.
By brazing the hydrocycodic compounds on the lignin, the wood quality nanoparticle is prepared, and the modification of the nano -sedimentation method is made to improve the crystallization performance of biodegradable plastic. At the same time, hydrophilic and hydrophobic modifications are used to use low -temperature plasma technology to build unilateral wet biodegradable non -woven fabrics.
Improving the spinning properties and unidirectional wetness of biodegradable plastic, maintaining the breathability and comfort of non -woven fabrics, and suitable for high -end fields such as sanitary napkins, diapers, masks, etc.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmentally friendly materials, and in particular relates to a unidirectional moisture-conducting biodegradable non-woven fabric and a preparation method thereof. Background Art
[0002] Nonwoven fabrics, also known as non-woven fabrics, are a new type of fiber product made from short fibers or filaments using different web-forming methods and consolidation technologies. They are soft, breathable, and have a flat structure. They are currently widely used in textile industries such as clothing and sanitary materials. Traditional nonwoven fabrics are mainly made of fibers such as polypropylene (PP) and polyethylene terephthalate (PET). These materials are difficult to biodegrade in the natural environment and will produce "white pollution" and microplastic pollution after use. Therefore, replacing traditional plastics with biodegradable plastics is considered to be the best way to fundamentally solve the problem of plastic pollution.
[0003] Most biodegradable plastics contain functional groups such as ester and amide groups on their molecular chains, which are easily decomposed by bacteria, fungi, etc. in nature, and eventually become carbon dioxide and water and enter the natural cycle. However, most biodegradable plastics have problems such as poor heat resistance and poor crystallization performance during processing. During the spinning process, fiber bonding and broken fibers are prone to occur, resulting in the inability to stretch and lay the web normally. In order to improve the above situation, methods such as reducing the molecular weight of the plastic, rapid cooling of the air outlet, and adding nucleating agents are usually used for modification. By adding nucleating agents for modification, the original homogeneous nucleation is transformed into heterogeneous nucleation in the molten state, which can greatly shorten the crystallization induction period and molding cycle, and significantly improve the heat resistance and crystallization performance of biodegradable plastics, thereby improving spinnability.
[0004] Traditional inorganic nucleating agents have small particle size, large specific surface energy and poor dispersibility, resulting in low nucleation rate. Small molecule organic nucleating agents have good dispersibility, but are easy to precipitate and have biological toxicity. Lignin is the second most abundant biomass on earth and has been widely used in the industrial field. As a natural plastic nucleating agent, lignin has a certain promoting effect in the crystallization process, but it is easy to agglomerate when used alone, and the nucleation effect is poor. In addition, the molecular structure of lignin contains a large number of hydrophilic functional groups such as hydroxyl groups, which have poor compatibility in plastics, limiting its further application in the field of biodegradable plastics. Lignin nanoparticles have good hydrophobic properties, good compatibility with biodegradable plastics, and biodegradable properties. Adding lignin nanoparticles can improve the crystallization properties of biodegradable plastics such as polybutylene adipate / terephthalate (PBAT) and improve their spinnability.
[0005] In addition, medical, textile, and sanitary non-woven fabrics are usually required to have one-sided hydrophilic properties. For example, the surface non-woven fabric of diapers needs to be hydrophilically modified to improve its liquid conduction ability. One-way moisture conduction has become an essential property of high-performance non-woven fabrics, and is particularly important for the application of non-woven fabrics in high-end fields. At present, the preparation methods of one-way moisture-conducting non-woven fabrics mainly include coating with hydrophilic additives, coating lamination, surface modification, etc. The hydrophilic coating enables the non-woven fabric to have better moisture conduction ability, but it will affect its air permeability. Patent CN205467700U discloses a method for preparing a one-way moisture-conducting non-woven fabric. The one-way moisture-conducting non-woven fabric is made of polypropylene as a raw material, and the hydrophilic spunbond layer on the outer surface and the hydrophobic spunbond layer on the inner surface are superimposed on each other by hot pressing, so that it has a one-way moisture-conducting function. Regardless of whether the coating or hot pressing method is used, it will affect the air permeability of the non-woven fabric, and the preparation process is relatively complicated.
[0006] Plasma surface treatment technology is easy to operate, green and environmentally friendly, and is often used for semiconductor surface treatment. Using plasma to treat the surface of non-woven fabrics will not change the material structure, and can maintain the good air permeability of non-woven fabrics. In addition, the treatment process is easy to operate and environmentally friendly, and can become a green and environmentally friendly alternative technology for non-woven fabric surface treatment. This technology etches the material surface through a variety of high-energy active ions such as ions, excited states and free radicals, and introduces specific surface functional groups, thereby changing the surface wettability of the material. Summary of the invention
[0007] In view of the poor spinnability and moisture conductivity of biodegradable materials such as PBAT, PBS, and PBST, the present invention provides a unidirectional moisture-conducting biodegradable non-woven fabric and a preparation method thereof. First, a hydrazide compound is grafted onto lignin, and a lignin nanoparticle nucleating agent is prepared by a nanoprecipitation method. The biodegradable plastic is further blended and modified to improve the crystallization performance of the biodegradable plastic, and a series of biodegradable non-woven fabrics are prepared. At the same time, the non-woven fabric has asymmetric wettability and unidirectional moisture-conducting properties through plasma hydrophilic and hydrophobic modification.
[0008] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: A method for preparing a unidirectional moisture-conducting biodegradable nonwoven fabric comprises the following steps: (1) Preparation of lignin nanoparticle nucleating agent: Filter pulping black liquor, acidify, wash with water, and dry to obtain purified lignin, dissolve the purified lignin in a sodium hydroxide solution with a pH of 10 to 12, heat to 50 to 70°C, add a hydrazide compound and a catalyst, and react for 1 to 4 hours to obtain grafted modified lignin; dissolve the grafted modified lignin in ethylene glycol, then add dropwise to a hydrochloric acid solution with a pH of 4, wash with water, and spray dry to obtain a lignin nanoparticle nucleating agent; (2) Preparation of biodegradable non-woven fabric: 88-98.3 parts of biodegradable polyester, 0.5-5 parts of lignin nanoparticle nucleating agent, 0.1-1 parts of dispersant, 1-5 parts of bio-based plasticizer, and 0.1-1 parts of anti-ultraviolet aging additive were weighed by weight, and the mixture was stirred for 5-10 minutes, and then the biodegradable modified particles were obtained by melt blending, water-cooled pelletizing, and drying. The biodegradable modified material was added to a spunbond non-woven fabric machine, and the spinning temperature, blowing power, induced draft power, winding speed, pulling speed, and pressure roller temperature were set to prepare the biodegradable non-woven fabric; (3) Preparation of unidirectional moisture-conducting biodegradable nonwoven fabric: Low-temperature plasma technology is used to perform hydrophilic and hydrophobic modifications on both sides of the biodegradable nonwoven fabric to obtain a biodegradable nonwoven fabric with unidirectional moisture-conducting function.
[0009] Furthermore, the pulping black liquor in step (1) is one or more of poplar, eucalyptus, masson pine, birch, straw, wheat straw, reed, bagasse, bamboo obtained by caustic soda method, sulfate method or sulfite method, and the lignin content in the pulping black liquor is 10-48%, and the density is 1.02-1.45 g / mL.
[0010] Furthermore, the hydrazide compound in step (1) is one of acetohydrazide, phenylacetohydrazide, p-methylphenylacetohydrazide, dimethylhydrazide, and nonanoic acid hydrazide, and the mass ratio of the hydrazide compound to the purified lignin is 1:5-10.
[0011] Furthermore, the catalyst in step (1) is one of benzyltriethylammonium chloride, tetrabutylammonium bromide and tetrabutylammonium chloride, and the mass ratio of the catalyst to the purified lignin is 1:5-10.
[0012] Furthermore, the lignin nanoparticle nucleating agent prepared in step (1) has a particle size of 100-500 nm, a water contact angle of 135-155°, and a thermal decomposition temperature of 260-270°C.
[0013] Furthermore, the biodegradable polyester in step (2) is one or more of polybutylene succinate (PBS), polybutylene succinate-co-butylene terephthalate (PBST), and polybutylene adipate / terephthalate (PBAT).
[0014] Furthermore, the dispersant in step (2) is one or more of barium stearate, polyethylene wax and polyethylene glycol; the bio-based plasticizer is one or more of epoxy soybean oil, dioctyl succinate, acetyl tributyl citrate and dioctyl sorbate; and the anti-ultraviolet aging additive is one or more of 2-hydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, methyl phenyl salicylate, Tinuvin 770, Tinuvin 783 and Chimassorb 944.
[0015] Furthermore, in step (2), the spinning temperature is 180-230° C., the blowing power is 50-60 Hz, the induced draft power is 40-50 Hz, the winding speed is 5-6 Hz, and the pulling speed is 3-4 Hz.
[0016] Furthermore, the hydrophilic modified gas in step (3) is any one of O2, N2, CO, CO2, and NH3, the modification power is 60-120 W, and the modification time is 1-5 min; the hydrophobic modified gas is one or more of CF4, C2F6, trimethylchlorosilane, hexamethyldisilazane, fluorosilane, and tetraethyl orthosilicate.
[0017] The present invention also provides the use of the unidirectional moisture-conducting biodegradable non-woven fabric prepared by the preparation method in sanitary napkins, diapers, masks, shoes and clothes.
[0018] Principle of the present invention: In order to solve the problem that traditional small molecule organic nucleating agents such as hydrazide compounds are easy to precipitate and difficult to biodegrade, small molecule hydrazide compounds are grafted onto lignin to solve the precipitation problem and improve its biodegradability, while also improving the compatibility of lignin nanoparticle nucleating agents with biodegradable resins.
[0019] In order to solve the problem of decreased air permeability of unidirectional moisture-conducting nonwoven fabrics, low-temperature plasma modification was used to replace the coating process to construct a unidirectional moisture-conducting biodegradable nonwoven fabric with asymmetric wettability. The problem of decreased air permeability of nonwoven fabrics due to surface modification was solved, and the problem of solvent environmental pollution caused by hydrophilic and hydrophobic finishing was avoided.
[0020] Compared with the prior art, the present invention has the following advantages and positive effects: (1) Improve spinnability: The present invention prepares lignin nanoparticle nucleating agents, which improve the crystallization behavior of biodegradable plastics such as PBAT, PBS, and PBST, shorten the molding temperature, increase the crystallinity, and enhance the spinnability of the materials. The improvement in the nucleation effect is mainly attributed to the use of lignin nanoparticles as crystal nuclei to change the crystallization of the materials and the induction of crystallization by hydrazide compounds, which work together to improve the crystallization performance of the materials. In addition, the lignin nanoparticle nucleating agent is a bio-based material with complete biodegradability, is not easily precipitated during use, and does not pose an environmental pollution risk.
[0021] (2) Excellent unidirectional moisture conduction performance: The present invention uses plasma modification to make the surface layer of the non-woven fabric have good liquid conduction ability (hydrophilic property), and uses plasma hydrophobic modification to make the bottom layer of the non-woven fabric have anti-rewet performance. Since the prepared non-woven fabric has asymmetric wettability, it has unidirectional moisture conduction performance.
[0022] (3) The unidirectional moisture-conducting biodegradable non-woven fabric prepared by the present invention has an environmentally friendly modification process and is flexible and simple to operate. The modified unidirectional moisture-conducting biodegradable non-woven fabric can still maintain its original air permeability and comfort, and can be applied to sanitary napkins, diapers, masks, shoes and clothing and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The DSC graphs of the biodegradable nonwoven fabrics in Examples 1 and 2 and Comparative Example 2 are shown.
[0024] Figure 2 It is the water contact angle of the unidirectional moisture-conducting biodegradable non-woven fabric in Example 4.
[0025] Figure 3 The scanning electron microscope images of the biodegradable non-woven fabric in Example 3 are: (a) before O2 modification and (b) after O2 modification.
[0026] Figure 4 This is the infrared spectrum of the biodegradable non-woven fabric in Example 3. DETAILED DESCRIPTION
[0027] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the contents of the present invention, which still fall within the scope of protection of the present invention.
[0028] The instruments and devices used in the present invention are also conventional instruments and equipment in this field. The pulping black liquor (Massonia pine black liquor, birch pulping black liquor, eucalyptus pulping black liquor, Massonia pine pulping black liquor) of the present invention comes from Fujian papermaking enterprises. The water vapor permeability coefficient test method involved in the present invention is: in accordance with GB / T 12704.1-2009 standard, the W3 / 031 water vapor permeability tester is used to measure the moisture permeability of the non-woven fabric, the test temperature is 38°C, the humidity is 90RH%, and 5 parallel samples are tested for each group of samples. The mechanical property test method involved in the present invention is: in accordance with GB / T24218.3-2010 standard, the XQ-1C tensile strength tester is used to measure the mechanical properties of the non-woven fabric, the sample is cut into a strip with a length of 300mm (test length is 200mm) and a width of 50mm, the tensile speed is 100mm / min, and 5 parallel samples are tested for each group of samples.
[0029] Example 1 1000g of black liquor of Masson pine (lignin content 46%, density 1.38g / mL) obtained by caustic soda pulping process was dissolved in 2000g of deionized water, stirred evenly and filtered to remove impurities, then 30% (V / V) hydrochloric acid solution was added dropwise to the filtrate, and the pH of the filtrate was adjusted to 2 to obtain purified lignin, which was washed with deionized water for 3 times, filtered and dried in vacuum at 60°C to obtain purified lignin. 100g of purified lignin was dissolved in 500ml of sodium hydroxide solution (pH=10), heated to 55°C and then slowly added with 10g of tetrabutylammonium chloride and 20g of p-methylphenylacetylhydrazine, stirred and refluxed, reacted for 3h, cooled, washed with deionized water, filtered, and vacuum dried at 60°C to obtain grafted modified lignin. The grafted modified lignin was dissolved in ethylene glycol, added dropwise to a hydrochloric acid solution of pH=4 by a peristaltic pump, washed with water and spray dried to obtain a lignin nanoparticle nucleating agent. The lignin nanoparticle nucleating agent prepared according to the above steps has a particle size of 125 nm, a water contact angle of 138° C., and a thermal decomposition temperature of 265° C.
[0030] 3000g PBS was placed in a vacuum drying oven and dried at 70°C for 12h; 35g lignin nanoparticle nucleating agent, 20g barium stearate, 35g epoxy soybean oil and 20g 2-(2'-hydroxy-5'-methylphenyl)benzotriazole were weighed and mixed with PBS resin in a mixer for 5min, melt-blended and water-cooled pelletized through a twin-screw extruder, and dried in a vacuum drying oven at 70°C for 12h to obtain PBS modified particles, which were then made into PBS biodegradable non-woven fabrics using a spunbond non-woven fabric machine.
[0031] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 110°C, 125°C, 135°C, 145°C, 150°C, 145°C, and 135°C, the die temperature is 130°C, and the screw speed is 300 rpm / min.
[0032] The temperatures in each zone of the spunbond nonwoven fabric testing machine are 130°C, 170°C, 200°C, 215°C, and 215°C, the die head temperature is 215°C, the blast power is 40HZ, the induced draft power is 50HZ, the traction frequency is 3HZ, the winding frequency is 4.8HZ, and the pressure roller temperature is 85°C.
[0033] PBS biodegradable nonwoven fabric was pasted on a flat plate, placed in a low-temperature plasma device, and vacuumed to 10 -3 ~10 -4 , CO was introduced for hydrophilic modification, the modification power was set to 80W, and the time was 1.5min. The hydrophilic modified surface layer was covered and placed in a low-temperature plasma device, and the vacuum degree of the cavity was evacuated to 10 -3 ~10 -4 , C2F6 was introduced for hydrophobic modification, the modification power was set to 90 W, the time was 1.0 min, and after modification, PBS biodegradable non-woven fabric with unidirectional moisture conduction function was obtained.
[0034] The water contact angle of the hydrophobic modified side of the PBS biodegradable nonwoven fabric prepared according to the above steps is 150.0°, the water contact angle of the hydrophilic modified side is 35.8°, the thickness is 0.18 mm, the water pressure resistance is: 10.62 KPa, and the moisture permeability is 5957 g / m 2 •d, the elongation at break is 46.23%, and the breaking strength is 12.28N.
[0035] Example 2 1000g of birch pulping black liquor (lignin content 38%, density 1.23g / mL) obtained by caustic soda pulping process was dissolved in 2000g of deionized water, stirred evenly and filtered to remove impurities, then 25% (V / V) sulfuric acid solution was added dropwise to the filtrate, and the pH of the filtrate was adjusted to 2 to obtain purified lignin, which was washed with deionized water for 3 times, filtered and dried in vacuum at 60°C to obtain purified lignin. 100g of purified lignin was dissolved in 500ml of sodium hydroxide solution (pH 10), heated to 55°C and then slowly added with 10g of benzyltriethylammonium chloride and 20g of phenylacetylhydrazine, stirred and refluxed for 2.5h, cooled, washed with deionized water, filtered, and vacuum dried at 60°C to obtain grafted modified lignin. The grafted modified lignin was dissolved in ethylene glycol, added dropwise to a hydrochloric acid solution with a pH of 4 by a peristaltic pump, washed with water and spray dried to obtain a lignin nanoparticle nucleating agent. The lignin nanoparticle nucleating agent prepared according to the above steps has a particle size of 135 nm, a water contact angle of 140° C., and a thermal decomposition temperature of 266° C.
[0036] 3000g PBS was placed in a vacuum drying oven and dried at 70°C for 12h; 30g lignin-based nucleating agent, 25g polyethylene wax, 35g acetyl tributyl citrate and 20g methyl phenyl salicylate were added respectively, mixed with PBS resin in a mixer for 5min, melt-blended through a twin-screw extruder, water-cooled and pelletized, and then dried in a vacuum drying oven at 70°C for 12h to obtain PBS modified particles, which were then made into PBS biodegradable non-woven fabrics using a spunbond non-woven fabric machine.
[0037] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 110°C, 125°C, 135°C, 145°C, 150°C, 145°C, and 135°C, the die temperature is 130°C, and the screw speed is 300 rpm / min.
[0038] The temperatures in each zone of the spunbond nonwoven fabric testing machine are 130°C, 170°C, 205°C, 220°C, and 220°C, the die head temperature is 220°C, the blast power is 40HZ, the induced draft power is 50HZ, the traction frequency is 3HZ, the winding frequency is 4.8HZ, and the pressure roller temperature is 85°C.
[0039] PBS biodegradable nonwoven fabric was pasted on a flat plate, placed in a low-temperature plasma device, and vacuumed to 10 -3 ~10 -4 , use N2 for hydrophilic modification, set the modification power to 85W, and the time to 1.0min. Cover the hydrophilic modified surface layer, put it into the low-temperature plasma equipment, and evacuate to 10 -3 ~10 -4, C2F6 was introduced for hydrophobic modification, the modification power was set to 80 W, the time was 1.5 min, and after modification, PBS biodegradable non-woven fabric with unidirectional moisture conduction function was obtained.
[0040] The water contact angle of the hydrophobic modified side of the PBS biodegradable non-woven fabric prepared according to the above steps is 145.0°, the water contact angle of the hydrophilic modified side is 36.2°, the thickness is 0.25 mm, the water pressure resistance is: 10.68 KPa, and the moisture permeability is 5414 g / m 2 •d, the elongation at break is 46.71%, and the breaking strength is 30.40N.
[0041] Example 3 1000g of eucalyptus pulping black liquor (lignin content 40%, density 1.27g / mL) obtained by caustic soda pulping process was dissolved in 2000g of deionized water, stirred evenly and filtered to remove impurities, then 30% (V / V) sulfuric acid solution was added dropwise to the filtrate, and the pH of the filtrate was adjusted to 2 to obtain purified lignin, which was washed with deionized water for 3 times, filtered and dried in vacuum at 60°C to obtain purified lignin. 100g of purified lignin was dissolved in 500ml of sodium hydroxide solution (pH 10), heated to 55°C and then slowly added with 10g of tetrabutylammonium bromide and 20g of dimethyl hydrazide, stirred and refluxed for 4h, cooled, washed with deionized water, filtered, and vacuum dried at 60°C to obtain grafted modified lignin. The grafted modified lignin was dissolved in ethylene glycol, added dropwise to a hydrochloric acid solution with a pH of 4 by a peristaltic pump, washed with water and spray dried to obtain a lignin nanoparticle nucleating agent. The lignin nanoparticle nucleating agent prepared according to the above steps has a particle size of 140 nm, a water contact angle of 135° C., and a thermal decomposition temperature of 268° C.
[0042] 3000g PBST was placed in a vacuum drying oven and dried at 70°C for 12h; 40g lignin nanoparticle nucleating agent, 25g polyethylene glycol, 40g dioctyl sorbate and 25g 2-hydroxybenzophenone were added respectively, mixed with PBST resin in a mixer for 5min, melt blended through a twin-screw extruder, water-cooled and pelletized, and then dried in a vacuum drying oven at 70°C for 12h to obtain PBST modified particles, which were then made into PBST biodegradable non-woven fabrics using a spunbond non-woven fabric machine.
[0043] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 150°C, 165°C, 175°C, 185°C, 180°C, 175°C, and 170°C, the die temperature is 170°C, and the screw speed is 300 rpm / min.
[0044] The temperatures in each zone of the spunbond nonwoven fabric testing machine are 160°C, 180°C, 210°C, 225°C, and 225°C, the die head temperature is 225°C, the blast power is 40HZ, the induced draft power is 50HZ, the traction frequency is 3HZ, the winding frequency is 4.8HZ, and the pressure roller temperature is 95°C.
[0045] PBST biodegradable nonwoven fabric was pasted on a flat plate, placed in a low-temperature plasma device, and vacuumed to 10 -3 ~10 -4 , use O2 for hydrophilic modification, set the modification power to 100W, and the time to 1.0min. Cover the hydrophilic modified surface layer, put it into the low-temperature plasma equipment, and evacuate to 10 -3 ~10 -4 , CHF3 was introduced for hydrophobic modification, the modification power was set to 80 W, the time was 2.0 min, and after modification, PBST biodegradable non-woven fabric with unidirectional moisture conduction function was obtained.
[0046] The water contact angle of the hydrophobic modified side of the PBST biodegradable nonwoven fabric prepared according to the above steps is 150.3°, the water contact angle of the hydrophilic modified side is 38.5°, the thickness is 0.18 mm, the water pressure resistance is: 11.47 KPa, and the moisture permeability is 5979 g / m 2 •d, the elongation at break is 50.81%, and the breaking strength is 35.45N.
[0047] Example 4 1000g of black liquor (lignin content 46%, density 1.38g / mL) obtained by caustic soda pulping process was dissolved in 2000g of deionized water, stirred evenly and filtered to remove impurities, then 20% (V / V) sulfuric acid solution was added dropwise to the filtrate, and the pH of the filtrate was adjusted to 2 to obtain purified lignin, which was washed with deionized water for 3 times, filtered and vacuum dried at 60°C to obtain purified lignin. 100g of purified lignin was dissolved in 500ml of sodium hydroxide solution (pH 10), heated to 65°C and then slowly added with 10g of benzyltriethylammonium chloride and 20g of phenylacetylhydrazine, stirred and refluxed for 4h, cooled, washed with deionized water, filtered, and vacuum dried at 60°C to obtain grafted modified lignin. The grafted modified lignin was dissolved in ethylene glycol, added dropwise to a hydrochloric acid solution with a pH of 4 by a peristaltic pump, washed with water and spray dried to obtain a lignin nanoparticle nucleating agent. The lignin nanoparticle nucleating agent prepared according to the above steps has a particle size of 125 nm, a water contact angle of 137° C., and a thermal decomposition temperature of 266° C.
[0048] 3000g PBAT was placed in a vacuum drying oven and dried at 70°C for 12h; 40g lignin nanoparticle nucleating agent, 20g barium stearate, 35g dioctyl succinate and 30g Tinuvin 783 were added respectively, mixed with PBAT resin in a mixer for 5min, melt blended by a twin-screw extruder, water-cooled and pelletized, and dried in a vacuum drying oven at 70°C for 12h to obtain PBAT modified particles, which were then made into PBAT biodegradable non-woven fabrics using a spunbond non-woven fabric machine.
[0049] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 130°C, 135°C, 145°C, 155°C, 150°C, 145°C, and 140°C, the die temperature is 140°C, and the screw speed is 300 rpm / min.
[0050] The temperatures in each zone of the spunbond nonwoven fabric testing machine are 150°C, 190°C, 210°C, 215°C, and 215°C, the die head temperature is 215°C, the blast power is 45HZ, the induced draft power is 60HZ, the traction frequency is 3HZ, the winding frequency is 4.8HZ, and the pressure roller temperature is 80°C.
[0051] The PBAT biodegradable nonwoven fabric was pasted on a flat plate and placed in a low-temperature plasma device and vacuumed to 10 -3 ~10 -4 NH3 was introduced for hydrophilic modification. The modification parameters were: power 100W, time 1.0min. The modification parameters were: power 80W, time 1min. The hydrophilic modified surface layer was covered and placed in a low-temperature plasma device. Vacuumed to 10 -3 ~10 -4 SF3 was introduced for hydrophobic modification, and the modification power was set to 90W for 1 min. After modification, a PBAT biodegradable nonwoven fabric with unidirectional moisture conduction function was obtained.
[0052] The water contact angle of the hydrophobic modified side of the PBAT biodegradable non-woven fabric prepared according to the above steps is 152.1°, the water contact angle of the hydrophilic modified side is 39.2°, the thickness is 0.15 mm, the water pressure resistance is: 10.69 KPa, and the moisture permeability is 5554 g / m 2 •d, the elongation at break is 230.6%, and the breaking strength is 10.31N.
[0053] Comparative Example 1 1000g of black liquor (lignin content 46%, density 1.38g / mL) obtained by caustic soda pulping process was dissolved in 2000g of deionized water, stirred evenly and filtered to remove impurities, then 28% (V / V) hydrochloric acid solution was added dropwise to the filtrate, and the pH of the filtrate was adjusted to 2 to obtain purified lignin, which was washed with deionized water for 3 times, filtered and dried in vacuum at 60°C to obtain purified lignin. 100g of purified lignin was dissolved in 500ml of sodium hydroxide solution (pH 10), heated to 65°C and then 10g of benzyltriethylammonium chloride and 20g of dimethylhydrazide were slowly added, stirred and refluxed for 3h, cooled, washed with deionized water, filtered, and vacuum dried at 65°C to obtain grafted modified lignin. The grafted modified lignin was dissolved in ethylene glycol, added dropwise to a hydrochloric acid solution of pH=4 by a peristaltic pump, washed with water and then spray dried to obtain a lignin nanoparticle nucleating agent. The lignin nanoparticle nucleating agent prepared according to the above steps had a particle size of 130 nm, a water contact angle of 140°C, and a thermal decomposition temperature of 266°C.
[0054] 3000g PBS was placed in a vacuum drying oven at 70°C and dried for 12h; 35g lignin nanoparticle nucleating agent, 20g polyethylene glycol, 35g dioctyl succinate and 20g 2-hydroxybenzophenone were added respectively, mixed with PBS resin in a mixer for 5min, melt blended through a twin-screw extruder, water-cooled and pelletized, and then dried in a vacuum drying oven at 70°C for 12h to obtain PBS modified particles, which were then made into PBS biodegradable non-woven fabrics using a spunbond non-woven fabric machine.
[0055] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 110°C, 125°C, 135°C, 145°C, 150°C, 145°C, and 135°C, the die temperature is 130°C, and the screw speed is 300 rpm / min.
[0056] The temperatures in each zone of the spunbond nonwoven fabric testing machine are 130°C, 170°C, 200°C, 215°C, and 215°C, the die head temperature is 215°C, the blast power is 45HZ, the induced draft power is 60HZ, the traction frequency is 3HZ, the winding frequency is 4.8HZ, and the pressure roller temperature is 80°C.
[0057] The water contact angles of the two sides of the PBS biodegradable nonwoven fabric prepared according to the above steps are 125.1° and 125.3° respectively, the thickness is 0.18 mm, the water pressure resistance is: 9.62 KPa, and the moisture permeability is 2865 g / m 2 •d, the elongation at break is 48.34%, and the breaking strength is 11.35N.
[0058] Comparative Example 2 3000g PBS was placed in a vacuum drying oven at 70℃ and dried for 12h; 25g polyethylene wax, 35g acetyl tributyl citrate and 20g methyl phenyl salicylate were added respectively, mixed in a mixer for 5min, melt blended in a twin-screw extruder, water-cooled and pelletized, and dried in a vacuum drying oven at 70℃ for 12h to obtain PBS modified particles. Subsequently, PBS biodegradable nonwoven fabric was made using a spunbond nonwoven fabric machine.
[0059] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 110°C, 125°C, 135°C, 145°C, 150°C, 145°C, and 135°C, the die temperature is 130°C, and the screw speed is 300 rpm / min.
[0060] The temperatures in each zone of the spunbond nonwoven fabric testing machine are 130°C, 170°C, 205°C, 220°C, and 220°C, the die head temperature is 220°C, the blast power is 40HZ, the induced draft power is 50HZ, the traction frequency is 3HZ, the winding frequency is 4.8HZ, and the pressure roller temperature is 85°C.
[0061] PBS biodegradable nonwoven fabric was pasted on a flat plate, placed in a low-temperature plasma device, and vacuumed to 10 -3 ~10 -4 , use N2 for hydrophilic modification, set the modification power to 85W, and the time to 1.0min. Cover the hydrophilic modified surface layer, put it into the low-temperature plasma equipment, and evacuate to 10 -3 ~10 -4 , C2F6 was introduced for hydrophobic modification, the modification power was set to 80 W, the time was 1.5 min, and after modification, PBS biodegradable non-woven fabric with unidirectional moisture conduction function was obtained.
[0062] The PBS biodegradable nonwoven fabric prepared according to the above steps is prone to broken threads, etc. The water contact angle of the hydrophobic modified side is 140.4°, the water contact angle of the hydrophilic modified side is 45.2°, the thickness is 0.25 mm, the water pressure resistance is: 8.09 KPa, and the moisture permeability is 4370 g / m 2 •d, the elongation at break is 43.22%, and the breaking strength is 21.34N.
[0063] Table 1 Application of lignin nanoparticle nucleating agents prepared in Examples 1-4 in the field of biodegradable plastics From the results in Table 1, it can be seen that after the biodegradable nonwoven fabrics of Examples 1-4 of the present invention are modified by plasma hydrophilicity and hydrophobicity, a biodegradable nonwoven fabric with asymmetric wettability is constructed, which significantly improves its moisture permeability. In Comparative Example 1, the wettability of both sides of the biodegradable nonwoven fabric that has not been modified by plasma is almost the same, so the nonwoven fabric does not have asymmetric wettability, resulting in a low moisture permeability. In Comparative Example 2, the biodegradable nonwoven fabric is not modified by adding lignin nanoparticle nucleating agent, resulting in poorer spinnability of the biodegradable nonwoven fabric than Example 2 and a lower difference in water contact angles on both sides of the nonwoven fabric, which indicates that the lignin nanoparticle nucleating agent can effectively improve the spinnability of biodegradable plastics and achieve further optimization of unidirectional moisture conduction performance.
[0064] Figure 1 The DSC graphs of the PBS biodegradable nonwoven fabrics prepared in Examples 1 and 2 and Comparative Example 2. The crystallization temperature of the PBS biodegradable nonwoven fabric with the addition of lignin nanoparticles increased from 58.8°C to 87.1°C, indicating that the addition of lignin nanoparticles can greatly shorten the crystallization induction period and molding cycle, thereby significantly improving the spinnability of the biodegradable plastic.
[0065] Figure 2 The unidirectional moisture-conducting biodegradable nonwoven fabric prepared in Example 4 was photographed using a contact angle tester to capture the change in its water drop contact angle over time. The unmodified PBAT biodegradable nonwoven fabric showed hydrophobicity. However, as time went on, the water droplets gradually penetrated into the interior of the biodegradable nonwoven fabric, and the contact angle dropped from 125.0° to 115.6°. The surface water drop contact angle of the PBAT biodegradable nonwoven fabric of Example 4 increased to 152.1° after SF3 plasma hydrophobic modification. The water contact angle did not change significantly within one minute, mainly because the surface of the nonwoven fabric contained fluorine-containing groups with hydrophobic properties after modification, which effectively inhibited the penetration of water droplets. After NH3 plasma hydrophilic modification, the contact angle dropped from 89.3° to 38.5°, mainly because after the hydrophilic modification of the nonwoven fabric, the surface oxygen-containing functional groups increased, causing its surface to change from hydrophobic to hydrophilic. Therefore, a biodegradable nonwoven fabric with a large difference in wettability was successfully constructed using plasma modification.
[0066] Figure 3 This is a scanning electron microscope image of the biodegradable nonwoven fabric prepared in Example 3. Figure 3 a is before O2 modification. Scanning electron microscopy shows that the fiber surface of the biodegradable nonwoven fabric is smooth and has good morphology before modification. The fiber morphology does not change much after modification, with only a small amount of scaly protrusions on the surface ( Figure 3 b). The fiber morphology on the surface of the nonwoven fabric after modification did not break, and the internal fiber morphology changed slightly. This shows that the modification only occurred on the fiber surface and would not have a significant impact on the mechanical properties of the nonwoven fabric.
[0067] Figure 4 This is an infrared spectrum of the biodegradable nonwoven fabric prepared in Example 3. The figure shows that the COC and C=O bond stretching vibration peaks of the biodegradable nonwoven fabric modified by O2 plasma are significantly enhanced, and hydrophilic oxygen-containing functional groups are introduced, so that the surface is changed from hydrophobic to hydrophilic.
[0068] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A method for preparing a unidirectional moisture-conducting biodegradable nonwoven fabric, characterized in that: The following steps are involved: (1) Preparation of lignin nanoparticle nucleating agent: Filter pulping black liquor, acidify, wash with water, and dry to obtain purified lignin, dissolve the purified lignin in a sodium hydroxide solution with a pH of 10 to 12, heat to 50 to 70°C, add a hydrazide compound and a catalyst, and react for 1 to 4 hours to obtain grafted modified lignin; dissolve the grafted modified lignin in ethylene glycol, then add dropwise to a hydrochloric acid solution with a pH of 4, wash with water, and spray dry to obtain a lignin nanoparticle nucleating agent; (2) Preparation of biodegradable non-woven fabric: weigh 88-98.3 parts of biodegradable polyester, 0.5-5 parts of lignin nanoparticle nucleating agent, 0.1-1 parts of dispersant, 1-5 parts of bio-based plasticizer, and 0.1-1 parts of anti-ultraviolet aging additive, and stir and mix for 5-10 minutes. Obtain biodegradable modified particles by melt blending, water-cooling pelletizing, and drying. Add the biodegradable modified material into a spunbond non-woven fabric machine, set the spinning temperature, blowing power, induced draft power, winding rate, traction rate, and pressure roller temperature, and make a biodegradable non-woven fabric; (3) Preparation of unidirectional moisture-conducting biodegradable nonwoven fabric: Low-temperature plasma technology is used to perform hydrophilic and hydrophobic modifications on both sides of the biodegradable nonwoven fabric to obtain a biodegradable nonwoven fabric with unidirectional moisture-conducting function.
2. The method for preparing a unidirectional moisture-conducting biodegradable nonwoven fabric according to claim 1, characterized in that: The pulping black liquor in step (1) is one or more of poplar, eucalyptus, masson pine, birch, rice straw, wheat straw, reed, bagasse, bamboo, obtained by caustic soda method, sulfate method or sulfite method, and the lignin content in the pulping black liquor is 10-48%, and the density is 1.02-1.45 g / mL.
3. The method for preparing a unidirectional moisture-conducting biodegradable nonwoven fabric according to claim 1, characterized in that: The hydrazide compound in step (1) is one of acetohydrazide, phenylacetohydrazide, p-methylphenylacetohydrazide, dimethylhydrazide and nonanoic acid hydrazide, and the mass ratio of the hydrazide compound to the purified lignin is 1:5-10.
4. The method for preparing a unidirectional moisture-conducting biodegradable nonwoven fabric according to claim 1, characterized in that: The catalyst in step (1) is one of benzyltriethylammonium chloride, tetrabutylammonium bromide and tetrabutylammonium chloride, and the mass ratio of the catalyst to the purified lignin is 1:5-10.
5. The method for preparing a unidirectional moisture-conducting biodegradable nonwoven fabric according to claim 1, characterized in that: The lignin nanoparticle nucleating agent prepared in step (1) has a particle size of 100-500 nm, a water contact angle of 135-155°, and a thermal decomposition temperature of 260-270°C.
6. The method for preparing a unidirectional moisture-conducting biodegradable nonwoven fabric according to claim 1, characterized in that: The biodegradable polyester in step (2) is one or more of polybutylene succinate, polybutylene succinate-co-butylene terephthalate, and polybutylene adipate / terephthalate.
7. The method for preparing a unidirectional moisture-conducting biodegradable nonwoven fabric according to claim 1, characterized in that: The dispersant in step (2) is one or more of barium stearate, polyethylene wax and polyethylene glycol; the bio-based plasticizer is one or more of epoxy soybean oil, dioctyl succinate, acetyl tributyl citrate and dioctyl sorbate; the anti-ultraviolet aging additive is one or more of 2-hydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, methyl phenyl salicylate, Tinuvin 770, Tinuvin 783 and Chimassorb 944.
8. The method for preparing a unidirectional moisture-conducting biodegradable nonwoven fabric according to claim 1, characterized in that: In step (2), the spinning temperature is 180-230° C., the blowing power is 50-60 Hz, the induced draft power is 40-50 Hz, the winding rate is 5-6 Hz, and the pulling rate is 3-4 Hz.
9. The method for preparing a unidirectional moisture-conducting biodegradable nonwoven fabric according to claim 1, characterized in that: The hydrophilic modified gas in step (3) is any one of O2, N2, CO, CO2, and NH3, the modification power is 60-120 W, and the modification time is 1-5 min; the hydrophobic modified gas is one or more of CF4, C2F6, trimethylchlorosilane, hexamethyldisilazane, fluorosilane, and tetraethyl orthosilicate.
10. Application of the unidirectional moisture-conducting biodegradable non-woven fabric prepared by the preparation method according to any one of claims 1 to 9 in sanitary napkins, diapers, masks, shoes and clothing.
Citation Information
Patent Citations
One -wayly lead wet non -woven fabrics
CN205467700U
Preparation method of biodegradable polylactic acid-fiberous composite
CN105968756A
Polylactic acid material as well as preparation method and product thereof
CN115895216A
Multifunctional particle additive for enhancement of toughness and degradation in biodegradable polymers
US11542392B1
Nanocellulose nucleating agents for crystallization of polylactides and other polymers
US20180118936A1
Cited By
Melt-blown spinning process method of bio-based degradable melt-blown non-woven fabric
CN120666500A